Functionality of System Components: Conservation of Protein Function in Protein Feature Space - Jensen, Lars Juhl (Cold Spring Harbor Laboratory Press, 2003)
Many protein features useful for prediction of protein function can be predicted from sequence, including posttranslational modifications, subcellular localization, and physical/chemical properties. We show here that such protein features are more conserved among orthologs than paralogs, indicating they are crucial for protein function and thus subject to selective pressure. This means that a function prediction method based on sequence-derived features may be able to discriminate between proteins with different function even when they have highly similar structure. Also, such a method is likely to perform well on organisms other than the one on which it was trained. We evaluate the performance of such a method, ProtFun, which relies on protein features as its sole input, and show that the method gives similar performance for most eukaryotes and performs much better than anticipated on archaea and bacteria. From this analysis, we conclude that for the posttranslational modifications studied, both the cellular use and the sequence motifs are conserved within Eukarya.